Survey Report: A Portrait of Muslims’ Socio-Religious Attitudes in Java - Jajat Burhanudin (Studia Islamika, 2010)
This report is based on two surveys, a baseline and an impact one, conducted by the PPIM in the framework of gauging the impact of the Islam and Development Program of The Asia Foundation in Jakarta. The first (baseline) survey was carried out in July 2008, just before the program started, while the second one was made after the program had ended in August 2009.Designed to measure the impact of the program, there were two categories of survey respondents: program participants (500 in each survey), who were randomly selected from the list of the names of those who participated in the program. They were interviewed before (July 2008) and after having attended the program (August 2009). As a control group, another 500 respondents were also interviewed in each survey. They had been randomly selected from the Muslim population all over Java.The questions posed during the surveys were related to the contents of the program, and were intended to illicit respondents’ views on such contemporary issues as civic values, democracy, socio-political and religious tolerance, pluralism, gender equity, and Islamism. Muslim responses to these ideas were analyzed in a comparative perspective between the baseline and impact surveys, and between program participants and non-participants. With this perspective, the survey was directed to discover the extent to which the program was able to contribute to the strengthening of the contemporary ideas mentioned above and of democracy in Indonesian socio-political spheres.DOI: 10.15408/sdi.v17i1.472